2020
DOI: 10.1108/jcre-01-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

The state of restroom facilities as a measure of cleaning service quality in an educational institution

Abstract: Purpose Sourcing decisions are important considerations in organizations’ strategic and policy resolutions. Given sometimes conflicting factors such as cost and financial implications, individual perceptions and motivation, health and safety of facility users, and organizational objectives, finding a balance and basis for making such decisions, presently and in future, is crucial. This paper aims to investigate the quality of services delivered by an insourced cleaning service team in a higher learning institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…However, it can also be provided using a mixed sourcing approach (Atkin and Brooks, 2015;Tannor et al, 2021) which has been observed to be the most common approach used by various institutions. Okoro et al (2020) and Tannor et al (2021) posited that the desired level of satisfaction should be achieved regardless of the sourcing approach used. This section presents these sourcing approaches, the context within which they are used, their pros and cons.…”
Section: Facilities Management Sourcing Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it can also be provided using a mixed sourcing approach (Atkin and Brooks, 2015;Tannor et al, 2021) which has been observed to be the most common approach used by various institutions. Okoro et al (2020) and Tannor et al (2021) posited that the desired level of satisfaction should be achieved regardless of the sourcing approach used. This section presents these sourcing approaches, the context within which they are used, their pros and cons.…”
Section: Facilities Management Sourcing Approachesmentioning
confidence: 99%
“…Such contractors focus more on performing their assigned roles in the contract and are not permanently part of the organisation. Outsourcing has also provided greater flexibility in employment strategies (Wickramasinghe et al, 2019;Okoro et al, 2020). Therefore, outsourcing FM can be an excellent strategy for large organisations to reduce operating costs, concentrate more on their core mission and primary activities and improve their competitive position (Oladokun, 2009).…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation
“…Internal learning refers to the situation where the employees get to learn new skills and knowledge while working as a team or individuals during the execution of routine and challenging tasks. External learning refers to the acquisition of skills, knowledge, and experience that the employees gain while working with suppliers, customers and other third-party service providers [24]. The organization which facilitates learning behaviour among employees develops competitive capabilities to handle a wide variety of scenario that occur in both internal and external environments [25].…”
Section: Internal and External Learningmentioning
confidence: 99%
“…Teachers' daily experiences in school are shaped in part by students; however, they are far from the only factor influencing their attitudes. Sometimes, the restroom facilities are considered as the level of service quality by the educational institutions [51]. While effective coordination at the school management team level helps reduce the amount of school violence [52], a lack of relational trust among actors and components in school management hampered community participation, which in turn hampered the overall progress of the community [53].…”
Section: Teaching Impedimentsmentioning
confidence: 99%